Emotional Intelligence Of Secondary Students Based On Mathematical Resilience And Domicile - Ayu Faradillah; Silvi Wulandari (Universitas Negeri Makassar, 2021)
This study is a study of students' emotional intelligence based on mathematical resilience and domicile. The method used in this research is descriptive qualitative. The total population in this study was 814 students in 12 junior and senior high schools spread across three different provinces, namely DKI Jakarta, Banten and West Java. In this study the subjects were selected based on the MR questionnaire, namely high, medium and low. Subjects selected based on MR category were selected based on their domicile and then the subject was given the second research instrument, namely emotional intelligence. The results showed that there was an influence between MR and emotional intelligence, namely SD subjects who had high MR also had high emotional intelligence, SB subjects who had moderate MR also had moderate emotional intelligence, and SJ subjects who had low MR also have low emotional intelligence. However, there is something interesting about the subject even though they have low MR and emotional intelligence on one of the indicators of SJ, they actually have a high enough motivation to learn, it makes unpleasant experiences as an enthusiasm for learning. Research results can vary or differ from one another based on research instrument used by researchers